Examining the Media’s Roles and Responsibilities, an Evaluation of Nigeria’s Development Toward the SDGs - Inobemhe, Kelvin; Santas, Tsegyu; Ogbesoh, Aminat Trust (UI Scholars Hub, 2024)
This paper examines the roles and responsibilities in the country’s development toward the Sustainable Development Goals (SDGs). The media in any society is fundamentally a development partner. Whether combating diseases or disseminating critical messages about development plans and actions to the public, the media is a key stakeholder. In Nigeria, the government, in collaboration with development agencies and other relevant stakeholders, has actively sought pathways to actualize the SDGs. The media are among these important stakeholders. The Nigerian press and media to serve the people and development across the nation present a good opportunity. However, this study observes that after SDGs were developed in 2015 and adopted by United Nations members, they remained unattended after the deadline. Against this backdrop, this study evaluates Nigeria’s development in light of the SDGs. Using a library research approach, the researchers examined the literature to interrogate the roles and responsibilities of the Nigerian media in achieving these goals. The study finds that the Nigerian media played vital roles in the processes leading to actualizing of the goals and identified key areas where improvement is required. It concludes the potential of the Nigerian press and media in paving their way to contribute further to the SDGs actualization and to the development of Nigeria.